CRISPR-Based Engineering of Plant-Associated Microbiomes: Challenges and Opportunities - Muhammad Zubair; Shahzain, Muqadas; Shakeel, Faiqa; Nabi Ullah; Bibi, Haleema; Zaka Ullah, Muhammad; Habib, Abdullah; Ahmad Shah, Syed Muhammad (Indus Journal of Bioscience Research, 2025)
In order to address global issues like food security and climate change, plant-associated microbiomes are essential to crop productivity, resilience, and sustainable agriculture. Microbiome engineering has been transformed by CRISPR-Cas technologies, which allow for precise genetic modifications to improve interactions between microbes and plants. The principles of CRISPR, their uses in modifying the rhizosphere, endosphere, and phyllosphere microbiomes, and their potential to enhance nutrient uptake, stress tolerance, and pathogen control are all thoroughly examined in this review. Along with addressing technical, environmental, and regulatory issues, it also highlights areas where multi-omics, artificial intelligence, and nanotechnology can be integrated. Prospects for the future place a strong emphasis on global cooperation for safe deployment, scalable field applications, and customized microbiomes. This review emphasizes how CRISPR is revolutionizing climate-resilient, sustainable agriculture.